Preparation of supported Co catalysts from Co–Mg–Al layered double hydroxides for carbon dioxide reforming of methane. (23rd February 2017) - Li, Dalin; Lu, Miaomiao; Xu, Shuping; Chen, Chongqi; Zhan, Yingying; Jiang, Lilong
Abstract: Mg(Al)O mixed oxide-supported Co catalysts were prepared by using Co–Mg–Al layered double hydroxides (LDHs) as precursors and their structural and catalytic properties for CH4 –CO2 reforming were studied. Upon calcination and reduction, Co–Mg–Al LDHs were decomposed to Mg(Co, Al)O mixed oxides and gave rise to highly dispersed Co metal particles with the mean size of ∼9–10 nm. The catalytic activity, stability, and coke resistance of Co/MgAl increased with the increase of Co loading. The 12%–15%Co/Mg3 Al catalysts showed high and stable activity as well as less coke deposition during 30 h of reaction at 1023 K. Sintering of Co particles was not clearly observed, indicative of good thermal stability of Co particles, and this could be attributed to the strong metal-support interaction between Co particles and Mg(Al)O. It was also found that the optimum LDHs-Co/MgAl catalyst exhibited superior coke resistance than the LDHs-Ni/MgAl catalyst. Particularly during 25 h of reaction at 873 K, the 12%Co/Mg3 Al catalyst showed much higher catalytic stability and much less coke deposition as compared to the 12%Ni/Mg3 Al catalyst, highlighting the great potential of using Co instead of Ni as an active catalyst for the CH4 –CO2 reforming. Highlights: Calcination and reduction of Co–Mg–Al LDHs gave ∼9–10 nm sized Co metal particles. Activity, stability, and coke resistance of Co/MgAl increased with the Co loading. 12%–15%Co/MgAl showed relatively high activity, stability, and coke resistance. Co/MgAl showed superior low-temperature stability and coke resistance than Ni/MgAl.